The Munich Lung Transplant Group: Intraoperative Extracorporeal Circulation in Lung Transplantation - Hoechter, Dominik J.; von Dossow, Vera; Winter, Hauke; Müller, Hans-Helge; Meiser, Bruno; Neurohr, Claus; Behr, Juergen; Guenther, Sabina; Hagl, Christian; Schramm, René (The Thoracic and Cardiovascular Surgeon, 2015)
Background This retrospective single-center study aimed to analyze transfusion requirements, coagulation parameters, and outcome parameters in patients undergoing lung transplantation (LuTx) with intraoperative extracorporeal circulatory support, comparing cardiopulmonary bypass (CPB), and extracorporeal membrane oxygenation (ECMO).Methods Over a 3-year period, 49 of a total of 188 LuTx recipients were identified being set intraoperatively on either conventional CPB (n = 22) or ECMO (n = 27). Intra- and postoperative transfusion and coagulation factor requirements as well as early outcome parameters were analyzed.Results LuTx patients on CPB had significantly higher intraoperative transfusion requirements when compared with ECMO patients, that is, packed red cells (9 units [5–18] vs. 6 units [4–8], p = 0.011), platelets (3.5 units [2–4] vs. 2 units [0–3], p = 0.034), fibrinogen (5 g [4–6] vs. 0 g [0–4], p = 0.013), prothrombin complex concentrate (3 iU [2–5] vs. 0 iU [0–2], p = 0.001), and tranexamic acid (2.5 mg [2–5] vs. 2.0 mg [1–3], p = 0.002). Also, ventilator support requirements (21days [7–31] vs. 5 days [3–21], p = 0.013) and lengths of ICU stays (36 days [14–62] vs. 15 days [6–44], p = 0.030) were markedly longer in CPB patients. There were no differences in 30-day and 1-year mortality rates.Conclusion These data indicate a perioperative advantage of ECMO usage with low-dose heparinization over conventional CPB for extracorporeal circulatory support during LuTx. Long-term outcome is not affected.
Keywords: extracorporeal circulation; cardiopulmonary bypass; ECMO; lung transplantation; anticoagulation